2017
DOI: 10.26719/2017.23.9.604
|View full text |Cite
|
Sign up to set email alerts
|

Mood and anxiety disorders among adolescent students in Jordan

Abstract: Les troubles de stress et d'anxiété chez des élèves adolescents en JordanieRÉSUMÉ Les troubles mentaux chez les adolescents ont des impacts négatifs sur des aspects concernant la santé et la vie quotidienne, mais les données relatives à leur prévalence manquent en Jordanie. La présente étude avait pour objectif d'estimer la prévalence des troubles de stress et d'anxiété et d'enquêter sur leur association avec le sexe et d'autres facteurs socio-démographiques chez des élèves adolescents. Une conception transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 27 publications
4
25
1
Order By: Relevance
“…[65] Similar to the previous Jordanian study female adolescents were significantly more likely to have mental disorders than males. [40] But in the previous presented studies in Palestine one study indicated boys more likely to be affected than girls [60] while the other showed not [61] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[65] Similar to the previous Jordanian study female adolescents were significantly more likely to have mental disorders than males. [40] But in the previous presented studies in Palestine one study indicated boys more likely to be affected than girls [60] while the other showed not [61] .…”
Section: Discussionmentioning
confidence: 98%
“…However, the researchers presented an explanation which might be that when both parents are present, any conflict between them might affect the mental health and anxiety levels of their adolescent offspring. [40] On the other hand, some studies were carried out to explore the prevalence of anxiety disorders and PTSD in particular after being exposed to several traumas such as war and conflict. According to a study conducted through assessing 3048 participants post conflict communities in Algeria, Cambodia, Ethiopia and Palestine.…”
Section: Anxiety Disorders and Ptsd World Widementioning
confidence: 99%
“…[65] Similar to the previous Jordanian study female adolescents were signi cantly more likely to have mental disorders than males. [40] But in the previous presented studies in Palestine one study indicated boys more likely to be affected than girls [60] while the other showed not [61] . Males are generally signi cantly less likely to seek and receive mental health services compared to females.…”
Section: Discussionmentioning
confidence: 98%
“…However, the researchers presented an explanation which might be that when both parents are present, any con ict between them might affect the mental health and anxiety levels of their adolescent offspring. [40] On the other hand, some studies were carried out to explore the prevalence of anxiety disorders and PTSD in particular after being exposed to several traumas such as war and con ict. According to a study conducted through assessing 3048 participants post con ict communities in Algeria, Cambodia, Ethiopia and Palestine.…”
Section: Anxiety Disorders and Ptsd World Widementioning
confidence: 99%
“…However, the researchers presented an explanation which might be that when both parents are present, any con ict between them might affect the mental health and anxiety levels of their adolescent offspring. [19] On the other hand, some studies were carried out to explore the prevalence of anxiety disorders and PTSD in particular after being exposed to several traumas such as war and con ict. According to a study conducted by assessing 3048 participants post-con ict communities in Algeria, Cambodia, Ethiopia, and Palestine.…”
Section: Background Anxiety Disorders and Ptsd Worldwidementioning
confidence: 99%